2015
DOI: 10.3109/03639045.2015.1033426
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies for the treatment of ungual onychomycosis

Abstract: The success rate with topical nail products has been minimal. The main reason for this poor success rate could be attributed to the lack of complete understanding of the pathophysiology of the disease and clinical pharmacokinetic data of drugs in the infected nail apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
0
28
0
3
Order By: Relevance
“…Early diagnosis of fungal infections is necessary to the appropriate decision of the antifungal therapy of election because some organisms are less likely to respond to certain antifungal agents. In fact, therapies for the treatment of ungual onychomycosis are different depending on the location of infection and infectious agents (yeast, dermatophytes and non‐dermatophytic moulds) . Therefore, accurate diagnosis of onychomycosis before treatment initiation, based on both clinical and laboratory examinations, may help the clinician to select the most proper therapy decreasing not only the clinical symptoms but also the economic loss due to expensive antimycotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of fungal infections is necessary to the appropriate decision of the antifungal therapy of election because some organisms are less likely to respond to certain antifungal agents. In fact, therapies for the treatment of ungual onychomycosis are different depending on the location of infection and infectious agents (yeast, dermatophytes and non‐dermatophytic moulds) . Therefore, accurate diagnosis of onychomycosis before treatment initiation, based on both clinical and laboratory examinations, may help the clinician to select the most proper therapy decreasing not only the clinical symptoms but also the economic loss due to expensive antimycotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…51 Nail plate excision and matricectomy are only rarely performed in selected cases. 16,52 In recent years, various laser devices include neodymium-doped yttrium aluminum garnet (Nd:YAG), diode, carbon dioxide (CO 2 ), and Erbium:glass (Er:Glass) have been used as an alternative modality for onychomycosis. Their mechanism of action is not yet exactly known.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In vivo studies employing brain microdialysis in rats demonstrated that intranasal administration of NGF formulation with 0.5% peppermint oil enhanced the bioavailability by ∼8 fold compared to rats administered with NGF alone [24][25][26]. The bioavailability of NGF in the brain could be enhanced by intranasal administration of peppermint oil.…”
Section: Alteration Of Membrane Permeability Using Permeation Enhancersmentioning
confidence: 99%